INSTRUMEN GERANTUNG PADA MASYARAKAT GAYO DI KABUPATEN ACEH TENGAH (KAJIAN ORGANOLOGI) - Desi Munawarah (Grenek: Jurnal Seni Musik, 2018)
This research aims to understand organological Instrument ‘Gerantung’, the process of making Gerantung Instrument and the technique of playing Gerantung Instrument onGayonesepeople in Central Aceh Regency where Mr. A.R. Mouse and Ceh (Sheikh) Kilang were craftsmen of Gerantung Instrument. This research located in Belang Mersah village, Lut Tawar district. The theoretical foundation is discussing about organology definition, traditional music, Gerantung Instrument, the process and technique of playing. Time research started from July until August 2017. The techniques of collecting data are observation, interview, documentation and literature review. This research resulted some conclusions: organological instrument Gerantung includes some parts such as holder, patch, resonance tube, hanger and booth. The processes of makingGerantung Instrument on Gayonese people in Central Aceh regency include some materials and equipments such as woods, jackfruit wood roots, pendulum, canvas, sanding machine, tools, machetes, wood chisel, wood saw, whittling knife and ruler. The steps of makingGerantung Instrument are first, measure the woods. Second, perforate the wood for sound resonance. Third, sculpt and cut the segment. Fourth, put pendulum on the hole. Last, put a canvas on top of pendulum to ease it swing. The techniques of playing Gerantung Instrument include some steps such as understand the scales of diatonic (Do, Re, Mi, Fa, Sol , La, Si, Do), understand hands position and when playing Gerantung Instrument is in standing position.